Making Strides Toward Health Equity: The Experiences of Public Health Departments. Issue 4 (July 2019) - Narain, Kimberly Danae Cauley; Zimmerman, Frederick J.; Richards, Jessica; Fielding, Jonathan E.; Cole, Brian L.; Teutsch, Steven M.; Rhoads, Natalie
Abstract : Objectives: We explored the definition of health equity being used by public health departments and the extent of engagement of public health departments in activities to improve health equity, as well as facilitators and barriers to this work. Design: We conducted 25 semistructured qualitative interviews with lead public health officials (n = 20) and their designees (n = 5). All interviews were transcribed and thematically analyzed. Setting: We conducted interviews with respondents from local public health departments in the United States (April 2017-June 2017). Participants: Respondents were from local or state public health departments that were members of the Big Cities Health Coalition, accredited or both. Results: Many departments were using a definition of health equity that emphasized an equal opportunity to improve health for all, with a special emphasis on socially disadvantaged populations. Improving health equity was a high priority for most departments and targeting the social determinants of health was viewed as the optimal approach for improving health equity. Having the capacity to frame issues of health equity in ways that resonated with sectors outside of public health was seen as a particularly valuable skill for facilitating cross-sector collaborations and promoting work to improve health equity. Barriers to engaging in work to improve health equity included lack of flexible and sustainable funding sources as well as limited training and guidance on how to conduct this type of work. Conclusions: Work to improve health equity among public health departments can be fostered and strengthened by building capacity among them to do more targeted framing of health equity issues and by providing more flexible and sustained funding sources. In addition, supporting peer networks that will allow for the exchange of resources, ideas, and best practices will likely build capacity among public health departments to effectively do this work.